Development, growth and finance of organizations from an Eastern European context : the 2015 Griffiths School of Management Annual Conference on Business, Entrepreneurship and Ethics (GSMAC) - Vaduva, Sebastian; Fotea, Ioan S.; Thomas, Andrew R. (Springer, 2017)
This book explores challenges and approaches to the development, financial management and growth of Eastern European organizations, both public and private. Including papers derived from the 2015 Griffiths School of Management Annual Conference on Business, Entrepreneurship and Ethics (GSMAC), organized by Emanuel University of Oradea, the authors provide a variety of strategies for growth and development in areas such as IT, medical management, marketing, entrepreneurship and family business. Collectively, these contributions provide a problem-solving framework that tackles such questions as: How are the growth and financial models of organizations changing? How should leadership in organizations adapt in order to ensure sustainable growth? How should educational concepts and methods be improved to help the next generation in the new global business environment? The rapid evolution of technology and innovation has changed the face of the business environment. With new actors in the global marketplace and new means of production, marketing and finance, businesses--particularly those in emerging regions, such as Eastern Europe--are faced with the pressure to rethink their structures and models from within. In this new economic climate, common issues such as corruption, risk, and customer satisfaction need to be examined from a globalized perspective. The goal of the 2015 GSMAC conference and the resulting papers is to help organizations and institutions in Eastern Europe and other developing regions formulate strategies and policies to thrive in this environment and promote sustainable management practices.
Keywords: Business -- Congresses.; Business enterprises -- Congresses.; Leadership -- Congresses.; Entrepreneurship -- Congresses.; Markets -- Congresses.; Business ethics -- Congresses.; elektronické knihy; electronic books